2020
DOI: 10.1007/s00261-020-02798-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of multiparametric resonance and biopsy in prostate cancer detection: comparison with definitive histological report after laparoscopic/robotic radical prostatectomy

Abstract: Purpose Magnetic Resonance Imaging (MRI) targeted biopsy increases overall detection rates and decreases the risk of clinically insignificant PCa detection. The aim of this retrospective study is to compare concordance rates regarding side of lesion and Gleason Score at fusion targeted/systematic biopsy and MRI with the definitive histologic report of prostatectomy specimen. Methods 115 patients underwent multiparametric (mp) MRI and successively fusion targeted/systematic biopsy. 107 patients, with a positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…Therefore, SB should not be omitted when performing TB. This is in line with a study by Rapisarda et al who found that agreement on final histological reporting was higher when SB was additionally performed on TB [19].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, SB should not be omitted when performing TB. This is in line with a study by Rapisarda et al who found that agreement on final histological reporting was higher when SB was additionally performed on TB [19].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, in another study by Borkowetz et al, the rates of concordance and upgrading were 54 and 44% [ 19 ]. Furthermore, another report by Raipsarda et al observed high concordance rates of 67% [ 24 ]. In consequence, compared to the current literature, the SB of our study showed lower concordance rates, but also lower upgrading rates.…”
Section: Discussionmentioning
confidence: 99%
“…Target biopsies or random biopsies can influence grading variation, as random biopsies can result in undergrading compared to target biopsies [26,34]. This is illustrated by the finding that concordance rates between biopsy and radical prostatectomy specimens improved after multiparametric magnetic resonance imaging-targeted biopsies [35,36]. It is possible that part of the variation was due to sampling variation.…”
Section: Discussionmentioning
confidence: 99%